KESESUAIAN LAHAN DAN KELAYAKAN EKONOMI PENGEMBANGAN KAKAO DI KECAMATAN TOMMO KABUPATEN MAMUJU - Hasyir, Faula; Ibrahim, Bakhtiar; Abdullah, Abdullah (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Indonesia is the third-largest cocoa (Theobroma cacao L.) producer in the world and the twelfth-largest exporter of cocoa, making this commodity one of the subsectors of agriculture with significant potential in the national economy and state revenue. However, cocoa productivity in Indonesia from 2019 to 2022 has not yet reached its optimal potential, with production in 2022 reaching 667.3 thousand tons. Cocoa exports from Indonesia over the past five years have been dominated by cocoa beans, accounting for 99% of total exports. Indonesian cocoa has strong competitiveness in international markets. One of the cocoa production centers in Indonesia is West Sulawesi, specifically in Mamuju Regency. This region produces high-quality Lindak cocoa with a distinct flavor and higher polyphenol content compared to cocoa from Côte d'Ivoire, Ghana, and Malaysia. However, the area for cocoa development in Tommo District, Mamuju Regency, has experienced a decline, impacting productivity over the past five years. This challenge is related to various factors, including land suitability, cultivation technology, and post-harvest management. To enhance cocoa production in the Tommo District, it is necessary to evaluate land suitability both qualitatively and quantitatively. This evaluation will identify limiting factors and estimate production value based on land use. The results of this evaluation can provide information regarding the economic feasibility of cocoa development in the area, which is expected to improve farmers' incomes and support sustainable agriculture.